Effect of Road Traffic Noise Pollution on Human Work Efficiency in Government Offices, Private Organizations, and Commercial Business Centres in Agartala City Using Fuzzy Expert System: A Case Study - Debasish Pal; Debasish Bhattacharya (Advances in Fuzzy Systems)
This study examines the problems of reduction of individual’s efficiency in his/her respective working places because of road traffic noise pollution in Agartala due to rapidly growing vehicular traffic. This paper deals with monitoring and modeling of the disturbances caused due to vehicular road traffic interrupted by traffic flow conditions on personal work performance. Total of two hundred seventy individuals from different road side Government Offices, Private Organizations and Commercial Business Centres on both sides of busy roads of the city were interviewed for attitudinal responses. Traffic volume count and noise indices data were collected simultaneously at six selected sites of the city. A relationship was developed between different traffic noise parameters and its harmful impact on work competency of individuals using MATLAB. Regression equations developed to predict the percentage of high annoyance among the individuals are fit based on noise parameters and parameters related to traffic movements. In addition, statistical analysis was also carried out between measured and predictive values of the percentage of highly annoyed group of individuals. The present model will draw the attention of the State Government and will help the policy maker to take the necessary steps to reduce this problem.